Respuesta :

Answer:

[tex]1652w-1652[/tex]  is equivalent to [tex]\left(2w-2\right)\left(826\right)[/tex]

In other words:

[tex]\left(2w-2\right)\left(826\right)=\:1652w-1652[/tex]

Step-by-step explanation:

Considering the expression

[tex]\left(2w-2\right)\left(826\right)[/tex]

solving

[tex]\left(2w-2\right)\left(826\right)[/tex]

[tex]=\left(826\right)\left(2w-2\right)[/tex]

[tex]\mathrm{Apply\:the\:distributive\:law}:\quad \:a\left(b-c\right)=ab-ac[/tex]

[tex]a=\left(826\right),\:b=2w,\:c=2[/tex]

[tex]=\left(826\right)\cdot \:2w-\left(826\right)\cdot \:2[/tex]

[tex]=826\cdot \:2w-826\cdot \:2[/tex]

[tex]=1652w-1652[/tex]

Therefore,

[tex]1652w-1652[/tex]  is equivalent to [tex]\left(2w-2\right)\left(826\right)[/tex]

In other words:

[tex]\left(2w-2\right)\left(826\right)=\:1652w-1652[/tex]